(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the diagnostic value of Computed Tomography (CT) in children with nephroblastoma (Wilms tumor). Materials and Methods: A descriptive study was conducted on 43 children under 15 years of age, including 32 patients with nephroblastoma and 11 with other malignant renal tumors, treated at the National Children’s Hospital from August 2023 to July 2024. Post-surgical histopathological results were obtained for all cases to serve as the gold standard. Results: The majority of patients were under 60 months old (range: 9 months to 10 years), with an equal gender distribution. Common clinical presentations included a palpable abdominal mass (75%) and hematuria (34.4%). The mean tumor size was 8.4 cm, with 84.4% of cases measuring >5 cm. CT findings showed that most tumors had well-defined margins (75%), heterogeneous density (65.6%), marked enhancement (75%), and necrosis (68.75%). Intratumoral calcification was absent in 87.5%, and hemorrhage was present in only 18.7%. Among CT signs, intratumoral calcification and the presence of a pseudocapsule yielded the highest diagnostic value (83.7%), while alteration of the renal contour had the lowest (65.1%). The three features with the highest sensitivity were the pseudocapsule sign, necrosis/hemorrhage, and intratumoral calcification. The three features with the highest specificity were the pseudocapsule sign, intratumoral calcification, and tumor margins. Conclusion: CT imaging is highly effective in diagnosing nephroblastoma and differentiating it from other pediatric tumors.